2020
DOI: 10.1038/s41467-020-19819-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multi-antigenic SARS-CoV-2 vaccine candidate using a synthetic poxvirus platform

Abstract: Modified Vaccinia Ankara (MVA) is a highly attenuated poxvirus vector that is widely used to develop vaccines for infectious diseases and cancer. We demonstrate the construction of a vaccine platform based on a unique three-plasmid system to efficiently generate recombinant MVA vectors from chemically synthesized DNA. In response to the ongoing global pandemic caused by SARS coronavirus-2 (SARS-CoV-2), we use this vaccine platform to rapidly produce fully synthetic MVA (sMVA) vectors co-expressing SARS-CoV-2 s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 61 publications
7
90
0
Order By: Relevance
“…At present, MVA serves as an advanced vaccine technology platform for developing new vector vaccines against infectious disease and cancer including emerging viruses (15). In response to the ongoing pandemic, the MVA vector vaccine platform allows rapid generation of experimental SARS-CoV-2specific vaccines (16). Previous work from our laboratory addressed the development of an MVA candidate vaccine against MERS with immunizations in animal models demonstrating the safety, immunogenicity and protective efficacy of MVA-induced MERS-CoV S-antigen specific immunity (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…At present, MVA serves as an advanced vaccine technology platform for developing new vector vaccines against infectious disease and cancer including emerging viruses (15). In response to the ongoing pandemic, the MVA vector vaccine platform allows rapid generation of experimental SARS-CoV-2specific vaccines (16). Previous work from our laboratory addressed the development of an MVA candidate vaccine against MERS with immunizations in animal models demonstrating the safety, immunogenicity and protective efficacy of MVA-induced MERS-CoV S-antigen specific immunity (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…This article is a US Government work. It is not subject to copyright under 17 USC The copyright holder for this preprint this version posted January 1, 2021. ; https://doi.org/10.1101/2020.12.30.424878 doi: bioRxiv preprint 5 (18), but animal protection studies have not yet been reported. However, protection has been obtained with related MVA-based SARS CoV-1 and MERS in animals (19)(20)(21)(22) and a MVA MERS vaccine was shown to be safe and immunogenic in a phase 1 clinical trial (23).…”
Section: Introductionmentioning
confidence: 99%
“…Other vaccines, including ones based on vesicular stomatitis virus (15), an alphavirus-derived replicon RNA (16), and an inactivated recombinant New Castle Disease virus (17) have shown protection in animal models. Immunogenicity in mice was found for a modified VACV Ankara (MVA)-based CoV-2 vaccine, (18), but animal protection studies have not yet been reported. However, protection has been obtained with related MVA-based SARS CoV-1 and MERS in animals (1922) and a MVA MERS vaccine was shown to be safe and immunogenic in a phase 1 clinical trial (23).…”
Section: Introductionmentioning
confidence: 99%
“…Vaccines based on mRNA and adenovirus vectors have demonstrated promising results in clinical trials and have received emergency regulatory approval (11)(12)(13)(14). Other candidate CoV-2 vaccines, including ones based on vesicular stomatitis virus (15), an alphavirusderived replicon RNA (16), an inactivated recombinant Newcastle Disease virus (17), and modified VACV Ankara (MVA) (18,19) are at early stages of evaluation.…”
mentioning
confidence: 99%